Efektivitas seminar pasar modal syariah terhadap minat berinvestasi generasi milenial - M. Adam Fernanda; Hesty Rahayu Pangestuti (Jurnal Investasi Islam, 2020)
Sharia Capital Market Seminar is one of the education and socialization programs organized by the Indonesia Stock Exchange (IDX). The program is one of the efforts made by the Indonesia Stock Exchange to increase public investment interests, especially millennials, which are still quite low due to lack of literacy on the Islamic capital market. This study aims to examine the effectiveness of the Sharia Capital Market Seminar on investment interests in millennial generation. This research is a qualitative research with a random sampling method using purposive sampling technique. The data source in this study is primary data obtained from interviews using online questionnaires via Google Form. The results of this study found that the Sharia Capital Market Seminar educational program was effective in moderating the interest in investing in millennials.